BANK SAMPAH: UPAYA PEMBERDAYAAN MASYARAKAT DAN PENANGANAN LINGKUNGAN - Munawir Munawir (BBM (Buletin Bisnis & Manajemen), 2015)
There are regulations of solid waste and kind of solid waste in their households. Thepeople to be responsible with their own solid waste by separating organic and nonorganic solid waste in their households. Organic solid waste will be processed to becomecompost as organic fertilizer for all plants. Non organic solid waste will be reuse andrecycle to become usefull things or sell them to trash collector. Take in hand by progresif,simultaneous and integrated of organic solid waste and non organic solid waste isreduse big volume of solid waste. One of method in handling non organic solid waste istrash bank.This research about trash, trash bank in Indonesia and the sample of NirwanaTrash Bank located in RW 07, Pedurenan Village, Karang Tengah, Tangerang City.Nirwana Trash Bank has been operating more than two years (since 12 th October 2012),number of member 80 person or only 22,15% of 361 households in RW 07, with 9personil manajement (8 female, 1 male).Keywords: regulations, integrated, reduse, reuse, recycle, trash bank.